Tethering of Tricuspid Valve Resulting from Aberrant Tendinous Cords Mimic Ebstein's Anomaly, Three‐Dimensional Echocardiography Approach. Issue 4 (21st January 2014) - Hadeed, Khaled; Hascoet, Sebastien; Dulac, Yves; Peyre, Marianne; Acar, Philippe
Mini‐Abstract We report the case of a neonate presented with respiratory distress and severe cardiomegaly. Two‐dimensional echocardiography revealed tethering of tricuspid valve with severe regurgitation. We used real time three‐dimensional echocardiography to clarify the mechanism of this regurgitation.